Neo classical security & development (Keselamatan & Pembangunan - KESBAN) concept in countering criminal insurgency in Eastern Sabah - Abdul Rahman Alavi (Tesis, 2023)
Security and Development or KESBAN is classical counterinsurgency framework that was employed as a tool in defeating the communist terrorist under the Communist Party of Malaya (CPM) banner. This study is aimed to engage the classical KESBAN concept complement with some value-added element stregthening the counterinsurgency framework as a neo-classical approach to confront criminal insurgency in Eastern Sabah prepetrated by the Abu Sayyah Group (ASG).The finding study of the study suggests that the neo-classical KESBAN concept is applicable in any insurgency situation. The study recommended future research studies on the "water village" resettlement program and the benefits of joint operations with Philipinnes military against the ASG.